ANALISIS CURAH HUJAN KOTA PADANG SAAT MADDEN JULIAN OSCILLATION PERIODE 1980-2010 - Sudiar, Nofi Yendri; Siregar, Plato M. (Sainstek : Jurnal Sains dan Teknologi, 2012)
Madden Julian Oscillation (MJO) is a phenomenon that affects the activity patterns of convective clouds and rainfall, thus this study has the objective to analyze the characteristics of the MJO with increased rainfall due to convective activity over Padang. Daily rainfall data observed in seven observation stations analizing wavelet power spectrum to determine the pattern of rainfall in the region, further correlation it with the MJO. Important results obtained based on rainfall data is Padang has equatorial pattern. Correlation between the results obtained with the strong MJO rainfall is -0.54 to -0.687 in phase 3 and phase 4 is  -0.564 to -0.69 with a confidence level of 90% -95%. These results indicate that strong MJO events in phase 3 and 4 do not directly affect the increase in precipitation, due to the phase difference and the lag at seven observation stations over Padang. Physically, out of phase and lag means that any strong MJO enters Padang occurs cloud growth process and after the strong MJO exit this area then who have formed the clouds turned into rain. For the above normal category, excess rainfall while strong MJO phase 3 is the observation station Simpang Alai and Tabing respectively 122% and 120%, as well as strong MJO phase 4 is the observation station of Gunung Sariak, Kasang, Gunung Nago, Batu Busuk and Ladang Padi sequential 118%, 116%, 123%, 119% and 117%. Keywords: MJO, rainfall, wavelet